MFI Acid Catalysts with Different Crystal Sizes and Porosity for the Conversion of Furanic Compounds in Alcohol Media. Issue 14 (6th February 2017) - Antunes, Margarida M.; Lima, Sérgio; Fernandes, Auguste; Magalhães, Ana L.; Neves, Patrícia; Silva, Carlos M.; Ribeiro, Maria F.; Chadwick, David; Hellgardt, Klaus; Pillinger, Martyn; Valente, Anabela A.
Abstract: Solid acid catalysts possessing MFI topology and different crystal sizes and porosities were explored for the conversion of carbohydrate‐biomass‐derived α‐angelica lactone and 5‐(hydroxymethyl)furfural, in 1‐butanol at T =120–170 °C, to give levulinate esters and furanic ethers. Micro/mesoporous microcrystalline catalysts were prepared by post‐synthesis base/acid treatments of ZSM‐5 zeolite; the influence of the desilication (base) conditions on the material properties was investigated. A nanocrystalline ZSM‐5 sample was synthesised by using hydrothermal, dynamic conditions and used as a reference material. A comparison of the catalytic performances of materials featuring different morphological, textural, and acid properties highlights a complex interplay between the acid and textural properties. The best‐performing catalyst (MZS0.6) was obtained by post‐synthesis‐treatment; fairly good catalytic stability was confirmed by catalyst recycling, contact tests, and characterisation of the spent catalyst. MZS0.6 was compared with the macrorecticular ion‐exchange resin Amberlyst‐15, chosen as a benchmark solid acid catalyst, in the two reaction systems. Abstract : Material changes : Zeolite ZSM‐5 can be modified to improve the potential as a heterogeneous catalyst for the conversion of biomass‐derived compounds. Solid acid catalysts possessing MFI topology and different crystal sizes and porosities were explored for the conversion of α‐angelica lactone (AnL) and 5‐(hydroxymethyl)furfural (HMF), in 1‐butanol at T =120–170 °C, to give levulinate esters (LE) and furanic ethers.